2022
DOI: 10.1021/acs.jpclett.2c00285
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive Skin Effect in Zeolites

Abstract: Effective contact and collision between reactants and active sites are essential for heterogeneous catalysis. Herein, we investigated molecular diffusion in more than 200 kinds of zeolites, and an intriguing "diffusive skin effect" was observed, whereby molecules migrated along the pore walls of zeolites (i.e., diffusion trajectories) because of the effect of the guest−host interaction and diffusion barrier. Furthermore, it was found that such a "diffusive skin effect" of zeolites would strongly promote the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…3l ), which was in accordance with the van der Waals analysis (Supplementary Fig. 1 ) of the ideal model 38 . This was further confirmed by ab initio MD simulations (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…3l ), which was in accordance with the van der Waals analysis (Supplementary Fig. 1 ) of the ideal model 38 . This was further confirmed by ab initio MD simulations (Supplementary Fig.…”
Section: Resultssupporting
confidence: 88%
“…In the procedure studied by Zhao et al, 22 the gas molecules are deleted after passing the DPR, which could mask velocity correlation effects and how a backscattered molecule will influence the entrance of a new molecule coming from the bulk region. This effect could be minimal for rough zeolites such as LTA, SAS, where a higher number of wall collisions is expected, 99 but highly important in soft-pore networks such as PON, TON, or AFI. Three-dimensional zeolites like MFI have a complex interplay of interactions because one molecule traveling through straight-channel pore could interact with molecules going through a sinusoidal-channel pore.…”
Section: Effects Attributable To the System Size And Entrymentioning
confidence: 99%
“…Experimentally, interfacial resistance to fluid transport in nanomaterials, as determined by fitting of diffusion models with finite surface permeability to transient uptake data, is believed to arise from surface pore blockages and structural distortions. , On the contrary, it has also been observed that the low surface permeability is largely nonstructural in origin, and not entirely due to blockages and surface defects, and that it may be a surface diffusion process occurring in a finite region in the vicinity of the pore mouth or external surface. In support, molecular dynamics (MD) simulations have suggested the existence of interfacial resistance even in ideal materials, albeit putatively. In such simulations, the excess resistance of a finite nanoscale material over that expected based on the diffusivity under periodic boundary conditions (i.e., in the absence of boundaries) is attributed to interfacial resistance, but without direct evidence for its existence or of the underlying mechanisms. These simulations and thermodynamic theories assume the interfacial resistance to reside in a very narrow zone in the solid in the vicinity of the external surface, whose length may be of the order of a nanometer, which is the distance over which the density profile develops, essentially resembling a sharp interface.…”
Section: Introductionmentioning
confidence: 99%